2016
DOI: 10.3389/fnagi.2016.00204
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline and Reorganization of Functional Connectivity in Healthy Aging: The Pivotal Role of the Salience Network in the Prediction of Age and Cognitive Performances

Abstract: Normal aging is related to a decline in specific cognitive processes, in particular in executive functions and memory. In recent years a growing number of studies have focused on changes in brain functional connectivity related to cognitive aging. A common finding is the decreased connectivity within multiple resting state networks, including the default mode network (DMN) and the salience network. In this study, we measured resting state activity using fMRI and explored whether cognitive decline is related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 74 publications
8
41
0
Order By: Relevance
“…While as distinct functional networks, the ECN and the SN tended to share positive FC (He et al, ), consistent with their increased activation during cognitive tasks compared to the deactivated DMN. Past studies on healthy ageing have demonstrated the importance of the connectivity profile with the SN (Chand, Wu, Hajjar, & Qiu, ; Onoda, Ishihara, & Yamaguchi, ), for instance, by improving the classification success on episodic memory performance and executive function between young and old participants (La Corte et al, ). Lower ECN‐SN FC may suggest that APOE ‐ɛ4 carriers had aberrant communication between networks critical for externally oriented cognition compared to noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“…While as distinct functional networks, the ECN and the SN tended to share positive FC (He et al, ), consistent with their increased activation during cognitive tasks compared to the deactivated DMN. Past studies on healthy ageing have demonstrated the importance of the connectivity profile with the SN (Chand, Wu, Hajjar, & Qiu, ; Onoda, Ishihara, & Yamaguchi, ), for instance, by improving the classification success on episodic memory performance and executive function between young and old participants (La Corte et al, ). Lower ECN‐SN FC may suggest that APOE ‐ɛ4 carriers had aberrant communication between networks critical for externally oriented cognition compared to noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, episodic memory is typically the most salient cognitive symptom of early AD and relies on the interplay of DMN and MTL activity (Miller et al, 2008;. Executive function also commonly declines in concert with episodic memory in aging and early AD, which may particularly implicate interplay between DMN network and salience networks (La Corte et al, 2016). Ongoing work in our group and others seeks to further differentiate the network alterations associated with aging and the earliest alterations specifically associated with the molecular pathologies of AD.…”
Section: Interpreting Default Mode/salience Effectsmentioning
confidence: 99%
“…Approximately 75% of the aging population report memory‐related problems (Koivisto et al, ). The decline in cognitive ability is not limited to neurodegenerative diseases, but also part of healthy aging (La Corte et al, ; van Geldorp et al, ) and has substantial consequences for quality of life (Hannigan, Coen, Lawlor, Robertson, & Brennan, ) and mortality (Connors et al, ). While most aging studies target individuals 65 years and older (e.g., Boutet, Milgram, & Freedman, ; Caselli, Chen, Lee, Alexander, & Reiman, ; Metzler‐Baddeley, Jones, Belaroussi, Aggleton, & O'Sullivan, ), recent research showed that brain structural and functional abnormalities can precede classical age‐related neurodegeneration decades earlier (Szoeke et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 75% of the aging population report memory-related problems (Koivisto et al, 1995). The decline in cognitive ability is not limited to neurodegenerative diseases, but also part of healthy aging (La Corte et al, 2016;van Geldorp et al, 2015) and has substantial consequences for quality of life (Hannigan, Coen, Lawlor, Robertson, & Brennan, 2015) and mortality (Connors et al, 2015).…”
Section: Introductionmentioning
confidence: 99%